Global economy: Slow recovery following deep recession - Claus Michelsen; Guido Baldi; Geraldine Dany-Knedlik; Hella Engerer; Stefan Gebauer; Konstantin Kholodilin; Sandra Pasch; Malte Rieth (DIW Weekly Report, 2020)
The coronavirus pandemic caused a global market crash in the first half of 2020. Following a massive slump of around four percent in the first quarter, global GDP decreased in the second by five percent. Lower rates of new infections, together with far-reaching monetary and fiscal policy measures to dampen the economic impact of the pandemic, ensure that production and the trust of consumers and firms will slowly return. Notably, China's quick economic recovery is inspiring hope. As long as the rate of new infections does not con- tinue to rise, global production in the third quarter is likely to increase markedly. DIW Berlin calculates that global produc- tion will shrink by 4.0 percent in 2020. During the forecast period, the global economy is likely to grow at quite strong rates of 5.8 percent in 2021 and 4.0 percent in 2022. However, risks still exist: if infection rates grow substantially again, a sig- nificant increase in insolvencies, combined with a rise in loan defaults, could destabilize the financial markets and ultimately threaten the solvency of some states.
Keywords: E32; E66; F01; 330; business cycle forecast; ecoomic outlook